2015
DOI: 10.1002/hbm.22790
|View full text |Cite
|
Sign up to set email alerts
|

Sensation‐to‐cognition cortical streams in attention‐deficit/hyperactivity disorder

Abstract: We sought to determine whether functional connectivity streams that link sensory, attentional, and higher-order cognitive circuits are atypical in attention-deficit/hyperactivity disorder (ADHD). We applied a graph-theory method to the resting-state functional magnetic resonance imaging data of 120 children with ADHD and 120 age-matched typically developing children (TDC). Starting in unimodal primary cortex—visual, auditory, and somatosensory—we used stepwise functional connectivity to calculate functional co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 61 publications
(94 reference statements)
4
51
2
Order By: Relevance
“…Age-related abnormalities were found in meta-analysis of cross-sectional studies of N-acetylaspartate in medial PFC (138). R-fMRI studies have also yielded cross-sectional results interpreted as consistent with maturational lags in ADHD (56;98;113;121;122). …”
Section: Emerging Models Of Brain Functional Organization In Adhdmentioning
confidence: 86%
See 1 more Smart Citation
“…Age-related abnormalities were found in meta-analysis of cross-sectional studies of N-acetylaspartate in medial PFC (138). R-fMRI studies have also yielded cross-sectional results interpreted as consistent with maturational lags in ADHD (56;98;113;121;122). …”
Section: Emerging Models Of Brain Functional Organization In Adhdmentioning
confidence: 86%
“…Children with ADHD, selected from group-matched ADHD-200 subsamples (n=120/group), showed greater FC within primary cortex and decreased step-wise FC to attention-regulatory networks; increased step-wise FC to DMN also characterized ADHD (98). …”
Section: Principal Measures and Approachesmentioning
confidence: 99%
“…The study using graph theory analysis to assess connectivity at a given path length (number of steps) from seeds in primary sensory cortices reported that ADHD was associated with increased short path (one or two steps) connections to multimodal cortices, and long path connections to medial PFC relative to controls. 68 ADHD was associated with reduced short path connections to frontoinsular and anterior cingulate cortices and reduced long path connections to dlPFC and inferior parietal cortices. 68 Recent studies in adults suggest normalization of some of these differences with remission of ADHD but not others.…”
Section: Neurobiologymentioning
confidence: 97%
“…68 ADHD was associated with reduced short path connections to frontoinsular and anterior cingulate cortices and reduced long path connections to dlPFC and inferior parietal cortices. 68 Recent studies in adults suggest normalization of some of these differences with remission of ADHD but not others. A study in adults with a childhood diagnosis of ADHD reported that persistent ADHD was associated with reduced connectivity within the DMN (medial PFC and PCC) compared with both controls and remitted ADHD, which did not differ ( Figure 3).…”
Section: Neurobiologymentioning
confidence: 97%
See 1 more Smart Citation